Automated water flow reallocation using level sensors and a control system for equitable distribution in rural neighborhoods of Juan Montalvo parish, Latacunga - De La Cruz, Tania; Figueroa Olmedo , J. (EASI: Engineering and Applied Sciences in Industry, 2025)
This paper analyzes and presents a proposal to automate the distribution of drinking water to four rural neighborhoods in Juan Montalvo Parish, Latacunga, aiming to optimize its allocation. For many years, the scarcity of water and the absence of a system for its efficient distribution has posed persistent challenges for households in rural areas of Ecuador. To address this issue, a water flow control proposal was developed, considering both the continuous availability of the resource, regardless of the season, and the population size of each neighborhood in Juan Montalvo. The proposed solution involves implementing a PID control system to regulate the proportional opening and closing of control valves. The valve opening percentages were designed based on the number of inhabitants in each neighborhood, ensuring an equitable distribution of water resources across the communities. Automating the drinking water distribution process represents a significant advancement in water resource management. This proposal minimizes waste by ensuring precise control of outflows to each neighborhood, contributing to the sustainable use of water resources.